DIAGNOSTICS AND SURGICAL TREATMENT TACTICS OF COLON DIVERTICULOSIS AT ELDERLY AND SENILE AGE PATIENTS - Akhmedov, M.A.; Mirzakhmedov, M.M.; Aripova, N.Y.; Isroilov, B.N.; Ivatov, M. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
To improve the results of surgical treatment of diverticulosis of the colon and its complications. Material and methods: Under observation were 176 patients with diverticular disease of the colon. 62 (35.3%) patients had an uncomplicated course of the disease, the remaining 114 (64.7%) were diagnosed with complicated colon diverticulosis. Results: The volume of surgical intervention in emergency cases was determined individually. In a serious condition, stage operations were performed, in particular, at the first stage, the affected part of the intestine was removed, limited to the formation of an ileo- or colostomy. Postoperative complications were observed in 10 (12.8%) patients. Conclusions: An indication for surgical treatment is all types of complications of diverticulosis of the colon.